Inerter and Its Application in Vibration Control Systems - Chen, Michael Z. Q.; Hu, Yinlong (Springer Nature Singapore : Imprint: Springer, 2019)
This book offers the first comprehensive introduction to the inerter, its successful application in Formula One racing, and other state-of-the-art applications in vibration control. It presents fundamental analysis results and design methods for inerter-based vibration control systems. Providing comprehensive information on the inerter, a pioneering mechanical element invented by Prof. Malcolm C. Smith at Cambridge University in 2002, it will be of considerable interest to readers with a background in control theory, mechanical vibration or related subjects. .